Beneficial Effects of Empagliflozin Are Mediated by Reduced Renal Inflammation and Oxidative Stress in Spontaneously Hypertensive Rats Expressing Human C-Reactive Protein - Malínská, Hana; Hüttl, Martina; Marková, Irena; Miklánková, Denisa; Hojná, Silvie; Papoušek, František; Šilhavý, Jan; Mlejnek, Petr; Zicha, Josef; Hrdlička, Jaroslav; Pravenec, Michal; Vaněčková, Ivana (Biomedicines, 2022)
Gliflozins (inhibitors of sodium-glucose cotransporter 2) show many beneficial actions beyond their antidiabetic effects. The underlying mechanisms of these additional protective effects are still not well understood, especially under non-diabetic conditions. Therefore, we analyzed the effects of empagliflozin in young (3-month-old) and adult (12-month-old) male spontaneously hypertensive rats (SHR) expressing human C-reactive protein (CRP) in the liver. SHR-CRP rats are a non-diabetic model of metabolic syndrome, inflammation, and organ damage. Empagliflozin was given in a daily dose of 10 mg/kg body weight for 8 weeks. Both age groups of SHR-CRP rats treated with empagliflozin had lower body weight, decreased weight of fat depots, reduced ectopic fat accumulation in the liver and kidneys, and decreased levels of plasma insulin and β-hydroxybutyrate. Empagliflozin effectively reduced ectopic renal fat accumulation, and was associated with decreased inflammation. Exclusively in young rats, decreased microalbuminuria after empagliflozin treatment was accompanied by attenuated oxidative stress. In adult animals, empagliflozin also improved left ventricle function. In conclusion, in young animals, the beneficial renoprotective effects of empagliflozin could be ascribed to reduced lipid deposition in the kidney and the attenuation of oxidative stress and inflammation. In contrast, hepatic lipid metabolism was ameliorated in adult rats.
Keywords: SGLT-2 inhibitor; SHR-CRP; age; gene expression; lipid metabolism